STRENGTHENING RELIGIOUS MODERATION THROUGH MULTICULTURAL EDUCATION - Juni Wando Purba; Mega Nurhayani Saragih (International Journal of Teaching and Learning, 2026)
Religious plurality is a gift of God and the wealth of the Indonesian State. Being said to be a gift of God certainly has the basis that the values contained in it as a principle for his followers to behave and behave where they are. In the context of religious plurality, interfaith relations must be positioned within the framework of humanitarian relations because interfaith relations that are positioned regardless of interfaith relations result in religion losing its meaning. The biggest threat in dividing the nation is conflict with a religious background. Religious moderation is not limited to resolving religious conflicts, but also to foster an attitude of national commitment; tolerance; nonviolent; and accommodating to all local cultures in the community. To create religious moderation in Christian Universities can be done through a multicultural educational learning model. This article was written using a literature study, with a descriptive qualitative approach.  The results of the study found that religious moderation in Christian Universities is categorized as good, but it still needs to be improved. These improvements can be made through multicultural educational learning models, namely: content integration, scientific construction, prejudice reduction, equal/fair education or equality in education, empowerment of higher education culture and social structures.